Quantization Structure of Orbital Oscillators and Mass Spectrum of Bosonic String - Duc, Dao Vong; Hang, Phuong Thi Thuy (Communications in Physics, 2008)
We consider a mechanism for removing tachyon field in bosonic string based on some modification of the structure of the commutation relations between coordinate orbital oscillators. This change causes the shifting of the mass spectrum for the component fields of the string field functional.